1998
DOI: 10.1046/j.1365-2249.1998.00521.x
|View full text |Cite
|
Sign up to set email alerts
|

Nasal tolerance in experimental autoimmune myasthenia gravis (EAMG): induction of protective tolerance in primed animals

Abstract: Nasal administration of microg doses of acetylcholine receptor (AChR) is effective in preventing the development of B cell-mediated EAMG in the Lewis rat, a model for human MG. In order to investigate whether nasal administration of AChR modulates ongoing EAMG, Lewis rats were treated nasally with AChR 2 weeks after immunization with AChR and Freund's complete adjuvant. Ten-fold higher amounts of AChR given nasally (600 microg/rat) were required to ameliorate the manifestations of EAMG compared with the amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…This may suggest that IgG2b and IgG2c are involved in the immunopathogenic process taking place in rat EAMG. IgG2b has been previously suggested to be involved in rat EAMG (41), but to our knowledge, there is no former information concerning the role of IgG2c in rat EAMG. Similar shifts in the AChR-specific IgG isotype profile were observed also when oral treatment was given before EAMG induction or when oral treatment was initiated during the chronic phase of EAMG (data not shown).…”
Section: Figurementioning
confidence: 86%
See 1 more Smart Citation
“…This may suggest that IgG2b and IgG2c are involved in the immunopathogenic process taking place in rat EAMG. IgG2b has been previously suggested to be involved in rat EAMG (41), but to our knowledge, there is no former information concerning the role of IgG2c in rat EAMG. Similar shifts in the AChR-specific IgG isotype profile were observed also when oral treatment was given before EAMG induction or when oral treatment was initiated during the chronic phase of EAMG (data not shown).…”
Section: Figurementioning
confidence: 86%
“…These studies have shown that mucosal administration of Torpedo AChR before immunization with AChR prevents the clinical manifestation of the disease and suppresses cellular and humoral responses to the AChR (27)(28)(29). When feeding with Torpedo AChR was performed during the acute phase of EAMG, it led to the elicitation of antibodies to Torpedo and to an increase in autoantibody titers to self muscle AChR (41,42). The priming effect on autoantibody levels induced by feeding with the xenogeneic and highly immunogenic Torpedo AChR and its limited availability hamper its application for therapeutic purposes.…”
Section: Figurementioning
confidence: 99%
“…Such a shift would be expected to lead to an increase in IgG1, which in the rat is regulated by Th2-type cells. IgG2b and IgG2c, which have been previously suggested to be involved in rat EAMG (2,23), are regulated by Th1 cells.…”
Section: Effect Of Anti-cd40l Treatment On Achr-specific Igg Isotypesmentioning
confidence: 87%
“…However, their capacity to produce anti-AChR IgG antibody, in particular IgG2b, was drastically reduced following immunization. Incidentally, IgG2b is highly myasthenogenic [31].…”
Section: Discussionmentioning
confidence: 99%